PENGARUH CAPITAL INTENSITY, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PERENCANAAN PAJAK PADA PERUSAHAAN SEKTOR PERTANIAN DAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2010-2015 - PERMATA DEWI, INTAN (Jurnal Akuntansi AKUNESA, 2018)
The purpose of this research is to analyze the influence of Capital Intensity, Leverage, and Size to tax planning that is controlled by ROA. Thus research is quantitative research using secondary data in the form of financial report from each company.Sample in this research using purposive sample of agricultural and mining sector companies which is listed on the Stock Exchanges of Indonesia in 2010 until 2015 and consistently generates profits. Total of samples in this research are 9 companies, 3 companies of agriculture sector and 6 companies of mining sector. The analysis technique used in this research is multiple linier regression analysis using SPSS 22. The results of this study proves that Capital Intensity and Leverage have no effect to tax planning, Size has negative effect to tax planning. The result of the coefficient determination showed 65,8% independent variable affect to dependent variable and 34,2% can be explain with the other variables.